Transformasi Pekarangan Sempit Melalui Pelatihan Hidroponik sebagai Upaya Peningkatan Ketahanan Pangan Keluarga: Transformation of Narrow Yards through Hydroponic Training as an Effort to Improve Family Food Security - Nurul Huda Fitriani; Nadya Astuti; Siti Faridah; Tina Finisia; Selly Asriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Family food security is a critical issue in urban areas, particularly among lower-middle-income communities that have not optimally utilized their home yards. This community service activity aims to improve the knowledge and skills of housewives in RT 024 RW 002, Tanjung Pagar Village, South Banjarmasin, in hydroponic cultivation to strengthen family food security. The target participants were 10 housewives selected based on yard availability and commitment to the program. The implementation methods included socialization, technical training on the Nutrient Film Technique and wick systems, technology application through starter kit distribution, assistance from cultivation to harvest, strengthening household financial literacy, and formative and summative evaluation. The results showed an increase in participants' knowledge and skills in seed sowing, AB Mix nutrient management, and pH and EC measurement. Narrow yards were successfully optimized into productive areas that sustainably support household food and economic needs.